Characteristics of sarcopenia by European consensuses and a phenotype score. Issue 2 (21st December 2019) - Jang, Il‐Young; Lee, Eunju; Lee, Heayon; Park, Hyungchul; Kim, Sunyoung; Kim, Kwang‐il; Jung, Hee‐Won; Kim, Dae Hyun
Abstract: Background: We aimed to assess the clinical characteristics of sarcopenia by the original and revised European Working Group on Sarcopenia in Older People (EWGSOP 1 and 2), and to propose a new sarcopenia phenotype score (SPS) to improve relevance of clinical outcomes. Methods: Analyses were performed in 1408 older adults of the Aging Study of PyeongChang Rural Area, a community‐based cohort in Korea. For sarcopenia definitions, we used EWGSOP 1, EWGSOP 2, and SPS, a new index counting number of abnormal domains among components of grip strength, gait speed, or muscle mass. Frailty status by the frailty index and the Cardiovascular Health Study frailty score was compared with sarcopenia measures. Prediction ability for composite outcome combining death and institutionalization due to functional decline was assessed among sarcopenia measures. Results: Generally, sarcopenia spectrum by both EWGSOP 1 and 2 was associated with worse functional status in parameters of geriatric assessments. However, population who were considered as sarcopenic by EWGSOP 1, but not by EWGSOP 2, showed increased risk of composite outcome and worse frailty status, compared with people who were classified as not sarcopenic by both EWGSOP 1 and 2. With SPS, dose–response relationship was observed with both frailty status and outcome prediction. Prediction for composite outcome was better in SPS than in EWGSOP 2 classification. Conclusions: A new SPS might be used to classify sarcopenic burden in older adults to resolve possible inconsistencies in phenotype correlation and outcome prediction of EWGSOP 2 criteria.